Magnetic Core–Shell Nanoparticles as Carriers for Olefin Dimerization Catalysts. Issue 12 (18th February 2013) - Ruhland, Thomas M.; Lang, Julian R. V.; Alt, Helmut G.; Müller, Axel H. E.
Abstract: We report the covalent support of functionalized nickel complexes on magnetic core–shell hybrid particles γ‐Fe2 O3 /SiO2 . Two completely different ways of connecting the particle with these nickel complexes were carried out. The first approach used the hydrosilylation method between the alkene‐substituted nickel complex and a silane. In a second approach, the particles were connected with the complexes by means of click chemistry (copper‐catalyzed Huisgen 1, 3‐dipolar cycloaddition). For this purpose, the nickel complexes were substituted with an alkyne moiety. Transmission and scanning electron microscopies, energy‐dispersive X‐ray diffraction, and FTIR spectroscopy were the methods employed to characterize the successful heterogenization of the nickel complexes. Abstract : On the basis of well‐characterized Fe2 O3 /SiO2 core–shell particles, the variable surface chemistry of the silica shell was used to combine the properties of the superparamagnetic nanoparticles with the catalytic character of nickel complexes in hybrid core–shell–corona nanoparticles to form heterogeneous nanocatalysts for olefin dimerization.